Long-Term Effect of Interferon on Keratinocytes That Maintain Human Papillomavirus Type 31 - Chang, Yijan E. (American Society for Microbiology, 2002)
The long-term effects of interferon treatment on cell lines that maintain human papillomavirus type 31 (HPV-31) episomes have been examined. High doses and prolonged interferon treatment resulted in growth arrest of HPV-positive cells, with a high percentage of cells undergoing apoptosis. These effects were not seen with interferon treatment of either normal human keratinocytes or cells derived from HPV-negative squamous carcinomas, which exhibited only slight decreases in their rates of growth. Within 2 weeks of the initiation of treatment, a population of HPV-31-positive cells that were resistant to interferon appeared consistently and reproducibly. The resistant cells had growth and morphological characteristics similar to those of untreated cells. Long-term interferon treatment of HPV-positive cells also resulted in a reduction in HPV episome levels but did not significantly decrease the number of integrated copies of HPV. Cells that maintained HPV genomes lacking E5 were sensitive to interferon, while cells expressing only the E6/E7 genes were resistant. In contrast, cells that expressed E2 from a tetracycline-inducible promoter were found to be significantly more sensitive to interferon treatment than parental cells. This suggests that at least a portion of the sensitivity to interferon could be mediated through the E2 protein. These studies indicate that cells maintaining HPV episomes are highly sensitive to interferon treatment but that resistant populations arise quickly.